POSTCOLONIAL PERSPECTIVES IN CONTEMPORARY ENGLISH NOVELS - Dr. Nileshkumar Ramshibhai Nandaniya (International Educational Journal of Science and Engineering, 2025)
Postcolonial literature has emerged as a significant field of study that examines the cultural, social, political, and psychological consequences of colonialism. Contemporary English novels often explore the experiences of societies that were once under colonial domination and continue to deal with its lasting legacy. This article analyses postcolonial perspectives in selected contemporary English novels and highlights how authors portray themes such as identity crisis, cultural hybridity, migration, social inequality, and resistance to colonial power structures. The study also discusses the conceptual framework of postcolonial theory developed by scholars such as Edward Said, Homi K. Bhabha, and Gayatri Chakravorty Spivak. Through the analysis of novels like Midnight’s Children, The White Tiger, and Half of a Yellow Sun, the article demonstrates how contemporary writers reinterpret colonial history and give voice to marginalized communities. It also examines the narrative techniques used in postcolonial fiction, including multiple perspectives, non-linear storytelling, linguistic hybridity, and the incorporation of indigenous cultural elements. The article concludes that contemporary English novels serve as powerful platforms for exploring the continuing impact of colonialism and for promoting cultural awareness and historical understanding in the modern world.